A composite material and its preparation method and its application in electrochemical sensor
Through the electrochemical sensor of Ti3C2Tx/Bi2Se3 composite material, the sensitivity and selectivity problems of trace heavy metal ions detection in sweat are solved, and low-cost, high-sensitivity non-invasive detection is achieved, which is suitable for portable devices.
Patent Information
- Application Number
- CN202411655111.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to achieve rapid, non-invasive and high-sensitivity detection of trace heavy metal ions in sweat. Traditional electrochemical sensor materials are costly, complex synthesis process and poor detection selectivity, and poor stability and toxicity of mercury electrodes.
The Ti3C2Tx/Bi2Se3 composite material was used to detect Pb and Cd ions in sweat by differential pulse voltammetry, and the synergistic effect of Bi2Se3 and Ti3C2Tx was used to improve the electrode's electroactive surface area and detection sensitivity.
It realizes high sensitivity detection of Pb and Cd ions in sweat, with low detection limit and low cost, suitable for portable equipment, wide detection range, suitable for mass production, and high sensitivity and high selectivity.
Smart Images

Figure HDA0005141936590000011 
Figure HDA0005141936590000012 
Figure HDA0005141936590000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical sensors, and in particular to a Ti3C2Tx / Bi2Se3 composite material and a preparation method thereof and application thereof in screen-printed electrochemical sensors. Background Art
[0002] Currently, non-invasive fluids mainly include tears, urine, saliva and sweat. Eye irritation can produce reflex tears and interfere with sensor readings. The content of saliva components can be significantly affected by food intake. Urine cannot be presented in a wearable form. In contrast, sweat, which is rich in physiological information, is the most ideal biofluid for continuous monitoring and non-invasive detection. As an easily accessible body fluid, sweat contains a variety of components related to human health, including electrolytes, glucose, lactate and heavy metal ions. Among heavy metals, Pb is an indispensable element in the human body, and excessive intake of Pb into the human body will damage the nervous system, skeletal system, blood circulation system, enzymes, and endocrine and immune systems. Cd is considered to be one of the most likely carcinogens. Chronic exposure to it may cause lung cancer, lung adenocarcinoma, prostate hyperplasia, renal insufficiency and hypertension. Therefore, it is of great significance to achieve rapid, trace, highly sensitive and highly selective detection of heavy metal ions in human sweat, which is also a hot and difficult research issue that has attracted much attention.
[0003] Traditional heavy metal analysis methods mainly include atomic absorption spectroscopy, atomic emission spectroscopy, inductively coupled plasma mass spectrometry, and atomic fluorescence spectroscopy. Although these detection methods have their own advantages, they are generally difficult to detect on site, the instruments are expensive, not easy to carry, require professional experimental operators, and have high operating costs. Electrochemical analysis has the characteristics of good selectivity, fast analysis speed, simplicity and low cost, and easy automation, and has been widely used in sweat analysis. The analytical performance of electrochemical sensors depends on the electrode materials. Materials with good adsorption can improve the detection efficiency of analytes. Electrode materials are an important component of electrochemical sensors. The substances to be tested will react on the surface of the working electrode, and the substances will be analyzed through the response signal. Screen-printed electrodes are suitable for POCT because of their low cost, miniaturization, and large-scale preparation. Therefore, this technology mainly starts from the structural regulation and surface modification of electrode materials, and builds an electrochemical sensing platform with excellent performance based on the development of new working electrode materials to achieve rapid, trace, high-sensitivity and high-selectivity detection of heavy metal ions.
[0004] Traditional electrochemical sensor materials often face various problems when detecting trace heavy metal ions in sweat. For example, precious metal nanomaterials are usually used to detect Pb and Cd ions, but their high cost and high requirements for the synthesis process have prompted people to explore other low-cost alternatives for metal ion detection. Due to the extremely low content of Pb and Cd ions in sweat (<100ppb), other traditional materials often encounter problems of insufficient sensitivity and poor selectivity for detection. In order to overcome these challenges, researchers began to explore the application of new nanomaterials. Different types of mercury electrodes and various electrochemical dissolution techniques have always been the most popular methods in the field of heavy metal electrochemical research. However, mercury has poor mechanical stability, which is not conducive to its application in flow systems and portable devices, and its chemical toxicity is very strong and difficult to handle and preserve.
[0005] Bismuth-based electrodes are an ideal material to replace mercury due to their low toxicity, high sensitivity, wide cathode potential range, insensitivity to dissolved oxygen, clear response signals, and low background current. They can also be used as a source of bismuth ions to form "alloys" with heavy metals. x ) is a two-dimensional transition metal carbide or nitride material with the advantages of ultra-low density, high specific surface area, large porosity and easy large-scale production. Compared with other materials, it has unique surface chemical properties, including hydrophilicity, reliable enzyme loading, rich surface functional groups, biocompatibility, excellent biocompatibility, etc., making it an excellent candidate material for electrochemical biosensors. However, using MXene (Ti3C2T x ) as an electrochemical biosensor, its performance is still insufficient.
[0006] At the same time, the prior art CN 108793166 B relates to a composite material of subgroup metal composite MXenes and its preparation method. The composite material of subgroup metal composite MXenes includes MXenes material and subgroup metal, the surface of the MXenes material is in-situ coated with the subgroup metal, and the subgroup metal is also distributed between the layers of the MXenes material. The preparation method includes: using a molten salt method, grinding the precursor Mn+1AXn phase material, subgroup metal salt and inorganic salt for 5 to 60 minutes, and reacting the obtained mixture at 300 to 800°C in an inert atmosphere for 1 to 48 hours, and then post-treating to obtain a composite material of subgroup metal composite MXenes. The composite material of the invention has the advantages of adjustable components, uniform composition, low cost, environmental protection and high efficiency, and has application prospects in the fields of electrode materials for electrochemical energy storage, wave absorbing materials, electromagnetic shielding materials, catalysts, etc. However, the temperature of the preparation method of the prior art is as high as 800°C, and the energy consumption is relatively high. The prepared material has an accordion structure, has a high content of metal elements, many impurities and a small specific surface area.
[0007] Prior art CN 109374711 B relates to an all-solid-state ion-selective electrode modified with MXene nanosheets, comprising an electrode substrate and a MXene nanosheet modification layer and an ion-selective polymer membrane sequentially coated on the electrode substrate; the MXene is a two-dimensional crystal of transition metal carbide or carbonitride, and its chemical formula is Mn+1Xn; wherein n=1, 2 or 3, M is a transition metal element, and X is carbon and / or nitrogen. However, this technology needs to be used in conjunction with an ion-selective polymer membrane, and the prepared all-solid-state ion-selective electrode needs to be immersed in a 0.01 mol / L calcium chloride solution for at least 24 hours for activation, and the detection preparation time is relatively long. At the same time, different ion-selective polymer membranes are required to detect different ions, and only a single ion can be detected at one time, which is not suitable for rapid and real-time detection. Summary of the invention
[0008] The object of the present invention is to provide a Ti3C2Tx / Bi2Se3 composite material with high sensitivity, a preparation method thereof and an application thereof in a screen-printed electrochemical sensor.
[0009] In order to achieve the above object, the present invention adopts the following technical solution:
[0010] A composite material obtained by compounding Bi2Se3 and Ti3C2Tx; Bi2Se3 and Ti3C2T x The mass ratio is 1-5:1.
[0011] In one preferred embodiment, in the composite material, Bi2Se3 and Ti3C2T x The mass ratio is 1-4.5:1.
[0012] In one preferred embodiment, in the composite material, Bi2Se3 and Ti3C2T x The mass ratio is 1.5-3.5:1.
[0013] In one preferred embodiment, in the composite material, Bi2Se3 and Ti3C2T x The mass ratio is 1.5:1.
[0014] The working electrode needs to have an excellent electroactive surface area to provide more active sites, thereby causing current changes. The present invention compounds Bi2Se3 and Ti3C2Tx to prepare a Bi2Se3 / Ti3C2Tx composite structure. The synergistic effect of the Ti3C2Tx and Bi2Se3 structures achieves high sensitivity and low detection limit of the sensor.
[0015] In one of the preferred embodiments, the Bi2Se3 is a flower-like structure formed by aggregation of multiple layered structures.
[0016] In one preferred embodiment, the maximum diameter of the monolithic layer structure is less than 2 μm, and the thickness of the monolithic layer structure is 20-90 nm. If the diameter is too large and the thickness is too large, the specific surface area will be reduced, and if the thickness is too small, the material is easy to break and it is difficult to form a flower-like structure.
[0017] During the preparation process, due to the polymerization heat, the monolithic layered structures usually aggregate to form flower-like structures, which have better electrocatalytic performance than the layered structures.
[0018] In one preferred embodiment, the Ti3C2Tx is a thin film structure.
[0019] In one preferred embodiment, the Ti3C2Tx is a two-dimensional thin film structure.
[0020] In one preferred embodiment, the single layer thickness of the thin film structure is 2-3 nm.
[0021] If the thickness is too large, MXene will be stacked together and the surface area will be reduced. The film has a high specific surface area, rich surface functional groups, and is easy to mass produce.
[0022] In one preferred embodiment, Ti3C2T x Attached to the surface of Bi2Se3, Ti3C2T x The maximum diameter of the single layer is larger than the maximum diameter of the monolithic layered structure of Bi2Se3.
[0023] Based on the same inventive concept, the present invention also claims a method for preparing the composite material, comprising the following steps:
[0024] S1. Preparation of Bi2Se3: SeO2 and Bi(NO3)3·5H2O are added to an alkaline solution, and after stirring, gallic acid monohydrate (GA) and TritonX-100 are added, and after mixing, the mixture is reacted at high temperature and high pressure for 20-28 hours. The obtained solution is centrifuged, washed, precipitated, and dried to obtain Bi2Se3;
[0025] S2. Preparation of Ti3C2T x / Bi2Se3 composite materials: Ti3C2T x and Bi2Se3 were ultrasonically mixed to obtain Ti3C2T x / Bi2Se3 composite materials.
[0026] In one preferred embodiment, the concentration of the alkaline solution in step S1 is 0.4-1.0M.
[0027] The concentration of alkali is directly related to the pH value and will greatly affect the synthesis process of Bi2Se3. When the pH is greater than 7, GA is easily oxidized, thus affecting the synthesis of Bi2Se3.
[0028] In one preferred embodiment, the alkaline solution in step S1 is a sodium hydroxide solution or a potassium hydroxide solution.
[0029] In one preferred embodiment, the mass ratio of SeO2 to Bi(NO3)3·5H2O in step S1 is 1:2.5-3.5.
[0030] In step S1, if the mass ratio of SeO2 to Bi(NO3)3·5H2O is too large or too small, the purity of the final product will be affected. By controlling the ratio, the product does not contain the impurity Bi2O3.
[0031] In one preferred embodiment, in step S1, SeO2 and Bi(NO3)3·5H2O are added to the alkaline solution and stirred at 60-80°C and 400-500 r / min for 20-40 min.
[0032] In one preferred embodiment, the mass ratio of GA to SeO2 in step S1 is 3-5:1.
[0033] If the content of GA is too little, the product will contain impurities such as Se and Bi2O3, and the layered structure cannot be agglomerated; if the content of GA is too much, it will affect the morphology of the layered structure agglomeration, causing the layered material to over-agglomerate, resulting in a clustered structure with poor electrocatalytic performance.
[0034] In one preferred embodiment, the mass ratio of TritonX-100 to SeO2 in step S1 is 5-10:1.
[0035] TritonX-100 will affect the morphology and size of Bi2Se3. Excessive content of TritonX-100 will increase the lateral area of the monolithic layered structure and reduce the thickness. If the content of TritonX-100 is too little, the Bi2Se3 layered structure cannot be aggregated into a flower-like structure. Both situations will affect the electrocatalytic performance.
[0036] The Bi2Se3 flower-like structure in the present invention is formed by a plurality of very thin layered structures gathered together. The key to the formation of the Bi2Se3 flower-like structure is the addition of GA and TritonX-100 in appropriate amounts.
[0037] In one preferred embodiment, the temperature of the high temperature and high pressure reaction in step S1 is 180-220°C, and the pressure is 1MPa-1GPa.
[0038] In one preferred embodiment, the washing in step S1 is to centrifuge the precipitate with high-purity water and anhydrous ethanol, the centrifugal speed is 7000-9000 r / min, and the centrifugal time is 3-7 min.
[0039] In one preferred embodiment, in step S2, Bi2Se3 is first prepared into a Bi2Se3 dispersion with a concentration of 3-7 mg / mL and then mixed with Ti3C2T x mix.
[0040] In one of the preferred embodiments, the Bi2Se3 dispersion is obtained by dispersing Bi2Se3 in water.
[0041] Based on the same inventive concept, the present invention also claims to protect the application of the composite material in preparing SPCE electrodes for detecting Pb and Cd ions.
[0042] A SPCE electrode for detecting Pb and Cd ions, comprising the Ti3C2T x / Bi2Se3 composite material was prepared.
[0043] The preparation method of the SPCE electrode for detecting Pb and Cd ions comprises: x Nafion and isopropanol are added to the / Bi2Se3 composite material, and ultrasonic mixing is performed to obtain a suspension; 3-7 μL of the suspension is dripped to modify the electrode, and the electrode is dried after modification to obtain the SPCE electrode.
[0044] In one preferred embodiment, the drying temperature is 50-60° C. and the drying time is 30-60 min.
[0045] In one preferred embodiment, Nafion and Ti3C2T x The mass ratio of / Bi2Se3 composite material is 0.8-1:1.
[0046] In one preferred embodiment, isopropyl alcohol and Ti3C2T x The mass ratio of / Bi2Se3 composite material is 30-35:1.
[0047] In one preferred embodiment, the electrode is pretreated with oxygen plasma before being modified.
[0048] In the process of detection with SPCE electrode, the single element solution standard substances of Pb and Cd are dripped on the working electrode. By applying a specific voltage waveform to the electrode and measuring the corresponding current response, as the base voltage changes continuously, the system continuously measures the differential current in multiple cycles, and plots these differential current values and the corresponding potential values into a curve, namely the differential pulse voltammetry curve. This curve usually presents a peak shape, and the position of the peak reflects the half-wave potential of the electrode reaction. The peak current is proportional to the concentration of the measured ions (i.e., Pb and Cd ions) in the solution. The peak potential can be used as the basis for qualitative analysis to make a standard curve, thereby realizing the quantitative analysis of the metal ion concentration in the solution.
[0049] Based on the same inventive concept, the present invention also claims protection for an electrochemical sensor, which comprises the composite material or the SPCE electrode for detecting Pb and Cd ions.
[0050] The present invention combines the advantages of Bi-based materials and MXene's good detection sensitivity to heavy metal ions to prepare Ti3C2T x / Bi2Se3 composite structure materials can well detect trace heavy metal ions using differential pulse voltammetry (DPASV). The trace Pb and Cd ions detected in artificial sweat can well cover the concentration range of Pb and Cd ions in sweat (0-100ppb).
[0051] The advantages of the present invention are:
[0052] (1) The present invention detects Pb and Cd ions in human sweat, which is a completely non-invasive detection method. It uses the electrochemical sensing principle to achieve a sweat Pb and Cd ion sensor with a low detection limit and high sensitivity. The sensor manufacturing method shown in the present invention is simple, easy to control variables, does not require complex instruments, has low cost, and can perform good Pb and Cd ion detection. The present invention makes full use of Ti3C2T x The method is simple, the film-forming area is controllable, and it can be prepared on a large scale, which meets the needs of future mass production. The present invention replaces the traditional electrolytic cell with a paper-based electrode, further reducing the detection cost and improving the portability and operability of the detection.
[0053] (2) The present invention is based on Ti3C2T x The screen-printed electrode modified with Bi2Se3 flower-like structure improves the speed of electron transfer and the specific surface area of the reaction. The prepared sensor has a wide detection range and a relatively low detection limit. 2+ The linear detection range is 10-150ppb, the detection limit is 2.88ppb, Pb 2+The linear detection range is 0-150ppb, and the detection limit is 3.45ppb. Therefore, the method of the present invention has the advantages of high sensitivity, wide detection range, good specificity, etc. 2+ and Pb 2+ The ultra-sensitive detection has important practical significance and has a good guiding significance for realizing on-site rapid and ultra-sensitive detection technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 Bi2Se prepared in Example 1 3, Ti3C2T x SEM images and elemental analysis of the Ti3C2T / Bi2Se3 composite material; a is the SEM result of the prepared Bi2Se3, b and c are the SEM results of Ti3C2T / Bi2Se3 in two different fields of view. x SEM results of / Bi2Se3 composite materials, d is the elemental analysis of Bi, e is the elemental analysis of Se, f is the elemental analysis of Ti, and g is the elemental analysis of C
[0055] Figure 2 Bi2Se prepared in Example 1 3, Ti3C2T x / Bi2Se3 composite material XRD pattern.
[0056] Figure 3 The bare carbon electrode, Ti3C2T x 、Bi2Se3、Ti3C2T x EIS spectrum (a), CV curve (b) and fitting linear curve (c) of the corresponding current peak of the / Bi2Se3 modified electrode.
[0057] Figure 4 Ti3C2T x DPV curves (a) of the electrode modified with Bi2Se3 composite to detect different concentrations of Pb and Cd ion solutions, the corresponding fitting curves (b) and (c), and the anti-interference diagram of the sensor (d). Stability test diagram (e). DETAILED DESCRIPTION
[0058] The present invention is not limited to the following specific embodiments. A person skilled in the art can implement the present invention in various other specific embodiments according to the contents disclosed in the present invention, or any simple changes or modifications made to the design structure and ideas of the present invention fall within the protection scope of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0059] In the following examples, hydrochloric acid, K3Fe(CN)6, and K4Fe(CN)6 were purchased from Sinopharm Chemical Reagent Co., Ltd. K3Fe(CN)6 and K4Fe(CN)6 were prepared into a potassium ferricyanide solution (2.5 mM [Fe(CN)6]) containing 0.1 M KCl electrolyte. 3- / 4- , pH = 7.4). Selenium dioxide (SeO2), bismuth nitrate pentahydrate (Bi(NO3)3·5H2O), and sodium hydroxide (NaOH) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., gallic acid monohydrate (GA) and Triton X-100 were purchased from Shanghai Yien Chemical Technology Co., Ltd., and amino-functionalized MXene dispersion (Ti3C2T x ) was purchased from Zhongke Leiming (Beijing) Technology Co., Ltd., artificial sweat was purchased from Shanghai McLean Biochemical Technology Co., Ltd., and Pb and Cd single element solution standard substances were purchased from Xiamen Haibiao Technology Co., Ltd. The electrochemical workstation was purchased from Shanghai Chenhua Instrument Co., Ltd., and the bare SPCE electrode and portable electrochemical test platform were jointly designed and developed by Changsha Sanjun Company. If the specific conditions are not specified in the examples, they are carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0060] Example 1
[0061] (1) Preparation of Bi2Se3 flower-like structure:
[0062] Dissolve 1.800g NaOH in 70mL high-purity water and stir magnetically for 25 minutes at 70℃ and 450r / min. Add 665mg SeO2 and 1940mg Bi(NO3)3·5H2O to the solution in turn, and continue to stir magnetically for 25 minutes at 70℃ and 450r / min. Add 2.35g GA and 5.0g TritonX-100 to the mixed solution and stir magnetically until uniform under the above conditions. Transfer the solution to a 100mL high-pressure reactor and react at 200℃ for 24h. After the reaction is completed, cool the reactor to room temperature, introduce the solution into a centrifuge tube, put it into a centrifuge, centrifuge it at 8000r / min for 5min, filter out the supernatant, and then use high-purity water and anhydrous ethanol to centrifuge it in the same way as above, and wash the sample 3 times each. Dissolve the Bi2Se3 prepared above in 150mL ultrapure water and mix it evenly by ultrasonication for 1h. Take 3 portions of 2 mL of the above solution in centrifuge tubes and dry them under vacuum at 60°C for 48 h. After drying, weigh the solution, subtract the mass of the empty centrifuge tube and divide by the volume to prepare a Bi2Se3 solution with a concentration of 5 mg / mL.
[0063] (2) Ti3C2T x Preparation of Bi2Se3 composite materials:
[0064] By mass ratio Bi2Se3:Ti3C2T x =1.5:1 to prepare a complex mixed solution, and ultrasonicate for 1 h to mix it evenly.
[0065] The prepared Bi2Se3, Ti3C2T x / Bi2Se3 composite materials were subjected to SEM inspection and elemental analysis of the material surface was performed using scanning electron microscopy (SEM) element mapping technology, such as Figure 1 As shown, a is the SEM result of the prepared Bi2Se3, b and c are the SEM results of Ti3C2T in two different fields of view. x SEM results of the Ti2Se3 / Bi2Se3 composite material, d is the elemental analysis of Bi, e is the elemental analysis of Se, f is the elemental analysis of Ti, and g is the elemental analysis of C. Bi2Se3 is a single-layered structure. Multiple thinner layered crystals agglomerate together after the solvent thermal reaction to form a flower-like feature (a), which is caused by agglomeration during the heating process. b and c are Ti3C2T x SEM image of the / Bi2Se3 composite material. Focusing on the surface of the Bi2Se3 flower-like material at low magnification, a few layers of Ti3C2T x Thin film. Ti3C2T x The film is attached to the Bi2Se3 surface, and the lateral size of the film is much larger than the Bi2Se3 flower-like structure. This structural feature can effectively increase the surface area of the material, providing more opportunities for the exposure of active sites, which is conducive to achieving a significantly large area and promoting material transfer on the film surface. Based on the elemental analysis of c, Figure 1 The results showed the presence of Bi, Se, Ti, and C elements, confirming that the Bi2Se3 nanoflower-like structures were successfully deposited on the surface of the Ti3C2 film. In addition, the uniform distribution of Bi, Se, Ti, and C elements demonstrated the strong bonding between Bi2Se3 and Ti3C2 nanosheets and the uniform coverage of the prepared material.
[0066] Bi2Se prepared in Example 1 3, Ti3C2T x / Bi2Se3 composite materials were tested by XRD, such as Figure 2 As shown, by comparing standard Bi2Se3 and Ti3C2T x The XRD spectrum of the / Bi2Se3 composite material shows that the composite material contains both Ti3C2T xThe results show that the two materials are well crystallized after synthesis. All Bi2Se3 diffraction peaks can be indexed according to the standard Bi2Se3 (JCPDS No.89-2008). No other phases are left in the sample, which indicates that the material contains purer Bi2Se3. In addition, the characteristic peak at 6.3° is very obvious. Through XRD analysis, this obvious characteristic peak corresponds to Ti3C2T x The results show that Ti3C2T x The composite with Bi2Se3 was successful.
[0067] Example 2
[0068] The composite materials prepared in the examples and comparative examples (Bi / Cu, Bi2O3 / SPCE, Bi / GO-SPE, alk-Ti2C3 and BiNPs@NPCMS nanocomposites), Ti3C2T x And a single Bi2Se3 modified SPCE electrode, the modification process is as follows:
[0069] 1. Ti3C2T x / Bi2Se3 suspension or separate solution was taken out from the 4°C refrigerator and placed at room temperature.
[0070] 2. Mix 1mL of Ti3C2T x 0.1 mL Nafion and 0.2 mL isopropanol were added to the mixed solution of Bi2Se3 in a certain ratio, and the two substances were mixed evenly by ultrasonication for 1 hour. 5 μL of the suspension was measured and modified on the working electrode by dripping. After each modification, the electrode was dried in an oven at 60°C for half an hour and stored in a refrigerator at 4°C.
[0071] The electrochemical performance was tested as follows:
[0072] ①Feasibility assessment of the sensor: Prepare a potassium ferrocyanide solution (2.5 mM [Fe(CN)6] 3- / 4- , pH = 7.4), potassium ferrocyanide solution was dropped on the electrodes prepared in steps (3) and (4) and a CV test was performed on them at a scan rate of 50mV-100mV, and the EIS curves of the four electrodes were tested.
[0073] ②Prepare artificial sweat containing Pb and Cd ion concentrations of 0ppb, 5ppb, 10ppb, 20ppb, 40ppb, 60ppb, 80ppb, 100ppb and 150ppb for differential pulse voltammetry test. Record the differential pulse voltammetry curve in the potential range of -1.4V to -0.6V, amplitude of 5mV and frequency of 15Hz. Explore the optimal test conditions by changing deposition potential, deposition time and other conditions, draw the DPASV curve and fit the peak current-Pb and Cd ion concentration linear regression curve.
[0074] EIS is widely used to evaluate the interfacial properties of modified electrodes. In order to monitor the gradual modification performance of the electrodes and the changes in the sensor interface characteristics, four electrodes were characterized using EIS analysis. In the Nyquist plot, the diameter of the semicircle in the high-frequency region corresponds to the charge transfer resistance (Rct), which directly reflects the electron transfer kinetics on the electrode surface. Figure 3 (a) shows the Nyquist plot of the stepwise electrode modification process obtained by fitting the data to an equivalent circuit model. Figure 3 As shown in (a), after modification with Bi2Se3, the Rct of the electrode reaches the maximum value. x After modification, due to Ti3C2T x The excellent conductivity of the material significantly reduced the Rct of the modified electrode. x / Bi2Se3 composite modification, the Rct value increases and falls within Ti3C2T x The values of SPCE for the modified electrode and the unmodified electrode are between 1.0 and 2.0. This phenomenon can be attributed to the fact that Bi2Se3 hinders the electrode and [Fe(CN)6] 3- / 4- The above results confirm that Ti3C2T x / Bi2Se3 electrochemical sensor was successfully constructed. In addition, the Ti3C2T x / Bi2Se3 / SPEC dynamics. Figure 3 As shown in (b), the peak current of the redox reaction increases as the scan rate increases from 50 mV / s to 100 mV / s. Figure 3 (c) A significant linear relationship between the peak current of the oxidation peak and the square root of the scan rate is observed. This linear relationship can be described by the following regression equation: Ipc = 6.678 + 4.670ν 1 / 2 , R 2 = 0.99 indicates a high fit. These results strongly suggest that the reaction mechanism on the electrode surface is mainly controlled by diffusion processes. In addition, the Randles-Sevcik equation can be used to calculate the Ti3C2T x / Bi2Se3 / SPEC (SPCE stands for screen-printed carbon electrode) has an electrochemical active area of 0.3052 cm 2 This value is the original electrode surface area (0.1256cm 2 ) by 2.43 times. By adjusting the amount of GA and TritonX-100 added, Bi2Se3 is made to be a separate non-aggregated flower-like shape, and then compounded with Ti3C2T x Applied to the SPEC electrode, the calculated electrochemical active area of the electrode is much lower than that of Ti3C2T x / Bi2Se3 / SPEC.
[0075] The composite materials prepared in the comparative example refer to the prior art, wherein the preparation method of Bi / Cu refers to the prior art (deCampos AM, Silva RR, Calegaro M L&Raymundo-Pereira P A. Design and Fabrication of Flexible Copper Sensor Decorated with Bismuth Micro / Nanodentrites to Detect Lead and Cadmium in Noninvasive Samples of Sweat[J]. Chemosensors 2022, 10(11): 446), the preparation method of Bi2O3 / SPCE refers to the prior art (Riman D., Jirovsky D, Hrbac J.&Prodromidis M I. Green and facile electrode modification by spark discharge: Bismuth oxide-screen printed electrodes for the screening of ultra-trace Cd(II)and Pb(II)[J]. Electrochemistry Communications, 2015, 50: 20-23), and the preparation method of Bi / GO-SPE refers to the prior art (Xing H, Zhang X, Zhai S, Mu W, Li C, Han X. Screen-printed electrode containing bismuth / graphene oxide hybrid for simultaneous detection of cadmium and lead ions[J]. Journal of Electroanalytical Chemistry, 2024, 961(15): 118222), the preparation method of alk-Ti2C3 refers to the prior art (Zhu X, Liu B, Hou H, et al. Alkaline intercalation of Ti3C2 MXene for simultaneous electrochemical detection of Cd(II), Pb(II), Cu(II) and Hg(II)[J].Electrochimica Acta, 2017, 248(10), 46-57). The preparation of BiNPs@NPCMS nanocomposites refers to Chinese patent application CN 117920992 A. By comparing the performance of these composites in detecting Pb and Cd ions in sweat, the comparison results are as follows:
[0076] The minimum detection limits of Pb and Cd ion concentrations in the present invention are much better than the minimum detection limits in the composite materials Bi / Cu and alk-Ti2C3. The linear detection range of Pb and Cd ion concentrations in the present invention is much larger than the linear detection range of the composite materials Bi2O3 / SPCE and Bi / GO-SPE, and the linear detection range in the present invention covers the concentration detection range of Pb and Cd ions in human sweat. The linear detection range of the composite materials Bi2O3 / SPCE and Bi / GO-SPE cannot completely cover the concentration detection range of Pb and Cd ions in human sweat. The detection sensitivity of Pb and Cd ions in the present invention (33.95μAμM -1 and 4.27 μA μM -1 ) is much higher than the sensitivity of BiNPs@NPCMS nanocomposites in detecting Pb and Cd ions (49.32 μA μM -1 and 40.67 μA μM -1 ).
[0077] Example 3
[0078] Based on Example 1, the mass ratio Bi2Se3:Ti3C2T x =1:1, 1.5:1, 2.5:1, 3.5:1, 4.5:1 to prepare 5 composite mixed solutions, the rest of which was consistent with Example 1, to obtain Bi2Se3 / Ti3C2T containing different Bi2Se3 masses x Composite materials.
[0079] The composite material was used to modify the SPCE electrode. The modification process was the same as in Example 2. When the Pb and Cd ion concentration was 100 ppb, the composite material Bi2Se3:Ti3C2T x When the mass ratio is 1.5:1, the peak currents of Cd ions and Pb ions are the largest, which are 4.9μA and 17.8μA respectively. x When the mass ratio is 1:1, the peak currents of Cd ions and Pb ions are 4.1μA and 15.5μA respectively. x When the mass ratio is 2.5:1, the peak currents of Cd ions and Pb ions are 4.3μA and 16.4μA respectively.x When the mass ratio is 3.5:1, the peak currents of Cd ions and Pb ions are 4.1μA and 16.2μA, respectively. x When the mass ratio is 4.5:1, the peak currents of Cd ions and Pb ions are 4.2μA and 15.7μA respectively. The same pattern exists under other concentration conditions. Comparing the peak currents under the same concentration conditions, the better composite material Bi2Se3:Ti3C2T x The mass ratio is 1.5-3.5:1, preferably 1.5:1.
[0080] Example 4
[0081] In order to verify the anti-interference ability of the detection method of the present invention, lactic acid, glucose, KCl and NaCl were selected to detect the composite material prepared in Example 1. 2+ and Cd 2+ The solution was supplemented with 5 mM lactic acid, 0.4 mM glucose, 0.1 mM ascorbic acid, 10 mM potassium chloride, 10 mM sodium chloride and 0.5 mM uric acid, and then the effects of Pb on 2+ and Cd 2+ The effect of peak current.
[0082] Under the optimized conditions of the experiment, the 2+ and Cd 2+ DPASV test was performed on artificial sweat. Figure 4 (a) It can be seen that Pb 2+ and Cd 2+ The peak current increases with the concentration, Cd 2+ The linear relationship is shown in the range of 10ppb-150ppb. Figure 4 (b), the linear equation is y = 0.038x + 0.953, R 2 =0.995, its sensitivity and detection limit are 0.038μA·ppb respectively -1 and 2.88ppb (S / N=3). Pb 2+ The linear relationship is shown in the range of 0ppb-150ppb. Figure 4 (c), the linear equation is y = 0.163x + 0.953, R 2 =0.996, and its sensitivity and detection limit are 0.163μA·ppb respectively -1 and 3.45ppb (S / N=3). Figure 4 (d) shows the Ti3C2T x / Bi2Se3 modified electrode. Lactic acid, glucose, ascorbic acid, KCL, and NaCl were selected for detection. 2+ and Cd 2+ The solution was supplemented with 5 mM lactate, 0.4 mM glucose, 10 mM KCl, 10 mM NaCl and 0.5 mM uric acid, and then the effects of Pb 2+ and Cd 2+ The effect of peak current. Figure 4 (d) It can be seen that lactic acid has an effect on Pb 2+ and Cd 2+ The effect is minimal, the peak current size and peak position are almost unchanged, and uric acid hardly changes Pb 2+ and Cd 2+ The peak current size will be reduced, but it will cause the peak position to move positively. Glucose will cause Pb 2+ and Cd 2+ The peak current decreases, but the peak position is hardly changed. The addition of potassium chloride and sodium chloride slightly affects the peak current positive shift and peak current size.
[0083] Example 5
[0084] In addition, the stability of the sensor was also evaluated. x The SPCE electrode sensor modified with Bi2Se3 was stored at 4°C and the DPASV response was continuously monitored for 7 days to detect the stability of the sensor. As shown in Figure 4(e), the activity of the sensor can maintain 91.7% of the initial level for Cd ions and 90.6% for Pb ions on the 7th day, indicating that the prepared sensor has good stability.
[0085] It should be noted that the above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A composite material, characterized in that: Composed of Bi2Se3 and Ti3C2T x Composite: Bi2Se3 and Ti3C2T x The mass ratio is 1-5:
1.
2. The composite material according to claim 1, characterized in that The Bi2Se3 is a flower-like structure formed by the aggregation of multiple layered structures.
3. The composite material according to claim 1, characterized in that The maximum diameter of the monolithic layer structure is less than 2µm, and the thickness of the monolithic layer structure is 20-90nm; the Ti3C2T x It is a thin film structure; the thickness of a single layer is 2-3nm.
4. The composite material according to any one of claims 1 to 3, characterized in that: Ti3C2T x Attached to the surface of Bi2Se3, Ti3C2T x The maximum diameter of the single layer is larger than the maximum diameter of the monolithic layered structure of Bi2Se3.
5. The method for preparing a composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Preparation of Bi2Se3: SeO2 and Bi(NO3)3·5H2O are added to an alkaline solution, and after stirring, gallic acid monohydrate and TritonX-100 are added, and after mixing, the mixture is reacted at high temperature and high pressure for 20-28 hours. The obtained solution is centrifuged, washed, precipitated, and dried to obtain Bi2Se3; S2. Preparation of Ti3C2T x / Bi2Se3 composite materials: Ti3C2T x and Bi2Se3 were ultrasonically mixed to obtain Ti3C2T x / Bi2Se3 composite materials.
6. The preparation method according to claim 5, characterized in that: The concentration of the alkaline solution in step S1 is 0.4-1.0 M; the mass ratio of SeO2 and Bi(NO3)3·5H2O is 1:2.5-3.
5.
7. The preparation method according to claim 5, characterized in that: In step S1, the mass ratio of GA to SeO2 is 3-5:1; the mass ratio of TritonX-100 to SeO2 is 5-10:
1.
8. The preparation method according to claim 5, characterized in that: The temperature of the high temperature and high pressure reaction in step S1 is 180-220°C, and the pressure is 1MPa-1GPa.
9. A SPCE electrode for detecting Pb and Cd ions, characterized in that: The composite material is prepared from the composite material according to any one of claims 1 to 4.
10. An electrochemical sensor, characterized in that: The electrochemical sensor comprises the composite material according to any one of claims 1 to 4 or the SPCE electrode for detecting Pb and Cd ions according to claim 9.
Citation Information
Patent Citations
Subgroup metal composites of MXenes, their preparation methods and applications
CN108793166B
An all-solid-state ion-selective electrode based on MXene nanosheets and its preparation method
CN109374711B
Electrochemical sensor for heavy metal detection, electrode modification material as well as preparation method and use method of electrode modification material
CN117920992A
Cited By
Bi2Se3 / Ti3C2Tx sweat heavy metal electrochemical sensor and preparation method thereof
CN121237248A